ANALYSIS OF THE VOLUME OF COMPETITIVE LOADS OF LEADING FOREIGN RIDERS IN MODERN CYCLING-HIGHWAY - Kubeev, A.V.; Oganesyan, A.A.; Savenkova, E.A. Savenkova; Matina, V.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the parameters of the volume of competitive load among the leading foreign racers in different age periods. Methods and structure of the study. In the course of the study, the results of the performances of foreign athletes (men) in road cycling in competitions included in the schedule of the International Cycling Union (UCI) for the period 1997-2021 were analyzed. The final sample included data from leading foreign athletes from 13 countries with different racing roles (n=31). The following parameters were taken as the main studied parameters (VCL): the total number of competition days - TNCD; the total distance (length) of the competitive load, expressed in kilometers, - TDCL. Results and conclusions. The result of the study was the determination of the confidence zones of the optimum volume of competitive load in cycling-highway for each age of athletes in the range from 18 to 33 years, which should be reflected in the federal standards of sports training in cycling. The authors recommend that, when forming the calendar plan of All-Russian and interregional highway cycling competitions (and its financial support), provide athletes with such a volume and nature of competitive starts that will allow them to fulfill the volumes of competitive loads recommended by the results of the study and get closer in this component of sports training to the leading cyclists of the world.